Airway inflammation in cystic fibrosis: molecular mechanisms and clinical implications. Issue 12 (23rd May 2013) - Cohen-Cymberknoh, Malena; Kerem, Eitan; Ferkol, Thomas; Elizur, Arnon
Abstract : Airway epithelial cells and immune cells participate in the inflammatory process responsible for much of the pathology found in the lung of patients with cystic fibrosis (CF). Intense bronchial neutrophilic inflammation and release of proteases and oxygen radicals perpetuate the vicious cycle and progressively damage the airways. In vitro studies suggest that CF transmembrane conductance regulator (CFTR)-deficient airway epithelial cells display signalling abnormalities and aberrant intracellular processes which lead to transcription of inflammatory mediators. Several transcription factors, especially nuclear factor-κB, are activated. In addition, the accumulation of abnormally processed CFTR in the endoplasmic reticulum results in unfolded protein responses that trigger 'cell stress' and apoptosis leading to dysregulation of the epithelial cells and innate immune function in the lung, resulting in exaggerated and ineffective airway inflammation. Measuring airway inflammation is crucial for initiating treatment and monitoring its effect. No inflammatory biomarker predictive for the clinical course of CF lung disease is currently known, although neutrophil elastase seems to correlate with lung function decline. CF animal models mimicking human lung disease may provide an important insight into the pathogenesis of lung inflammation in CF and identify new therapeutic targets.